Amine Metabolism Is Influenced by Dietary Protein Source - Kar, Soumya K.; Jansman, Alfons J. M.; Schokker, Dirkjan; Kruijt, Leo; Harms, Amy C.; Wells, Jerry M.; Smits, Mari A. (Frontiers in Nutrition, 2017)
Growth in world population will inevitably lead to increased demand for protein for humans and animals. Protein from insects and blood plasma are being considered as possible alternatives but more research on their nutritional quality and health effects is needed. Here we studied the effect of dietary protein source on metabolism and metabolic amine profiles in serum and urine of mice. Groups of mice were fed semi-purified diets containing 300 g/kg of either soybean meal (SBM), casein (CAS), partially de-lactosed whey powder (DWP), spray dried plasma protein (SDPP), wheat gluten meal (WGM) or yellow mealworm (YMW). Feed and water intake as well as body weight gain were measured for 28 days. After 14 and 28 days serum and urine samples were collected for measurement of a large panel of amine metabolites. Metaboanalyst 3.0 was used for analysis of the raw metabolic data. Out of 68 targeted amine metabolites, we could detect 54 in urine and 41 in blood serum. Dietary protein sources were found to have profound effects on host metabolism, particularly in systemic amine profiles, considered here as an endo-phenotype. We recommend serum over urine to screen for the amine metabolic endo-phenotype based on partial least squares - discriminant analysis. We concluded that metabolites like alpha-aminobutyric acid and 1-methylhistidine are sensitive indicators of too much or too little availability of specific amino acids in the different protein diets. Furthermore, we concluded that amine metabolic profiles can be useful for assessing the nutritional quality of different protein sources.